(untitled) (LIS TODAY, 2021)
This paper attempts to describe brief outline about latest trends, tools and technologies which are being started used in management and service areas of libraries. The emergence of ICT and its effect and impact via new technologies in libraries can be understood after going through this paper. The paper tries to pick such technologies which are becoming very famous among library and information science professionals due to its positive potential to implement and use it in LIS field. This paper tries to show how computer, mobile, internet and related technologies have capacity to go deep inside of library and information sector and having excellent power to manage libraries, library resources and can serve its users.